BACKGROUNDS FOR THE GLOBAL SOCIOLOGY OF EDUCATION - Viktoria A. Ivanova (Высшее образование в России)
The paper discusses new methodological aspects in the analysis of scientific environment in the sociology of education. It focuses on the new elements in the structure of this branch of sociology that exceed the limits of national and local researchers’ communities and become possible due to global spread of new IT and scientific communications, open resources of research data. The paper points at the global sociology of education as a reality that sets new conditions for researchers.